The “Prosta mova” as Linguistic Phenomenon in the Grand Duchy of Lithuania (Exploration of the Lexical Material of the Tyapinsky’s Gospel as Compared to the Ostrog Bible) - Андреевна Смирнова, Екатерина (Slavistica Vilnensis, 2009)
Scientists have various opinions on the written language of Lithuanian Rus’ of the sixteenth and seventeenth centuries, which is referred to as the “prosta mova”. “There is no any systematic description of this language and its grammar, first of all in comparison with Polish and Old Church Slavonic” (Garzdaniti 1999, 169). At the lexical level, V. Tyapinsky’s Gospel includes Ukrainian, Byelorussian and Polish borrowings. But there is no doubt that the basis of this text is Slavic.